2021
DOI: 10.1089/andro.2021.0007
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase in the Human Brain

Abstract: The aromatase cytochrome P450 (P450arom) enzyme, or estrogen synthase, which is coded by the CYP19A1 gene, is widely expressed in a subpopulation of excitatory and inhibitory neurons, astrocytes, and other cell types in the human brain. Experimental studies in laboratory animals indicate a prominent role of brain aromatization of androgens to estrogens in regulating different brain functions. However, the consequences of aromatase expression in the human brain remain poorly understood. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 140 publications
(164 reference statements)
0
13
0
Order By: Relevance
“…Results thus far show that depletion of circulating estrogen via OVX results in a loss of neuroprotection by cytisine. Cells in the brain are steroidogenic and express aromatase (AROM), which is the primary cytochrome P450 enzyme ( CYP19A1) that synthesizes 17-β-estradiol in the brain 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Results thus far show that depletion of circulating estrogen via OVX results in a loss of neuroprotection by cytisine. Cells in the brain are steroidogenic and express aromatase (AROM), which is the primary cytochrome P450 enzyme ( CYP19A1) that synthesizes 17-β-estradiol in the brain 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Estimates are per 1 standard deviation (SD) increase in the trait. to estrogens in regulating brain functions (Azcoitia et al, 2021). Notably, the epileptogenic effect of estradiol has also been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Among the instrumental variables of estradiol, two (rs3751591, rs7173595) were in the gene CYP19A1 , which encodes the aromatase cytochrome P450 (P450arom) enzyme, or estrogen synthase. The estrogen synthase converts androgens to estrogens, and previous experimental studies in laboratory animals have indicated a prominent role of brain aromatization of androgens to estrogens in regulating brain functions ( Azcoitia et al, 2021 ). Notably, the epileptogenic effect of estradiol has also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Aromatase inhibitors (AI) are potentially active for the treatment of BCBM as they lower both serum and CSF concentrations of estradiol [ 38 ]. However, the only publications suggesting AI (or tamoxifen) have activity for HR + BCBM are case series and reports [ 39 43 ].…”
Section: Discussionmentioning
confidence: 99%